Inovasi Pemanfaatan Buah dan Sayur Menjadi Smoothie Drink Untuk Meningkatkan Imunitas Tubuh di Masa Pandemi Covid-19 - Nur Syahraeni; Fuad AKbar (Jurnal Pengabdian Masyarakat Hasanuddin (JPMH), 2021)
One form of community service at the college level is real work (KKN) lectures. KKN is a form of activity where community service is performed by the student as well as off-the-books and off-the-books. The success of activities carried out by students can be seen from the benefits people feel after the work program. At this level of unhas wave of 105, students are called upon to create a work program related to the theme "the ambassador's change in covid-19 prevention behavior and 2020 pilkada supervision." Since more communities drink less fruit and vegetables, the activities of the individual work program they perform on this activity is an innovation in fruit and vegetable smoothies to increase body immunity during the covid-19 pandemic. Smoothies are powdered fruit or vegetables that blend a blender. The implementation of this work program will be held from January 21, 2020 to January 22, 2021, located in Teddaopu Village, Wajo Regency, South Sulawesi. In the making of these smoothies used raw materials like bananas, apples, and spinach. As a result of this activity, it is hoped that both social media users and the neighborhood community will learn that vegetables and fruits can be combined to produce healthy drinks like smoothies that boost body immunity.